2006
DOI: 10.1590/s0100-69162006000100011
|View full text |Cite
|
Sign up to set email alerts
|

Validação do modelo ClimaBR em relação ao número de dias chuvosos e à precipitação total diária

Abstract: RESUMO:Este trabalho foi realizado com o objetivo de validar o modelo ClimaBR no que se refere à geração de séries sintéticas de precipitação total diária em diferentes localidades brasileiras. Para tanto, foram geradas séries sintéticas de precipitação para 12 localidades, escolhidas de forma distribuída, para que todas as diferentes regiões de precipitação homogênea do País fossem contempladas. A partir das séries pluviométricas, disponíveis nas estações meteorológicas das localidades selecionadas, o ClimaBR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
15

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 6 publications
(6 reference statements)
0
2
0
15
Order By: Relevance
“…For all studied stations and return periods, Table 10 demonstrates that composed series of N+M years had the lowest error values compared to N-year ones. In relation to the average relative errors, ZANETTI et al (2006), aiming to generate daily total rainfall synthetic series through ClimaBR model in 12 Brazilian locations, concluded that distribution simulations by number of rainy days, from the Markov model, were representative, even in situations of large regional weather variability. The number of years was relevant both for Markov chain transition probabilities and for Gamma distribution parameters in order to obtain the lowest relative mean squared errors.…”
Section: Resultsmentioning
confidence: 99%
“…For all studied stations and return periods, Table 10 demonstrates that composed series of N+M years had the lowest error values compared to N-year ones. In relation to the average relative errors, ZANETTI et al (2006), aiming to generate daily total rainfall synthetic series through ClimaBR model in 12 Brazilian locations, concluded that distribution simulations by number of rainy days, from the Markov model, were representative, even in situations of large regional weather variability. The number of years was relevant both for Markov chain transition probabilities and for Gamma distribution parameters in order to obtain the lowest relative mean squared errors.…”
Section: Resultsmentioning
confidence: 99%
“…O gerador climático usado foi o ClimaBR 2.0 -Gerador de Séries Sintéticas de Dados Climáticos (Oliveira, 2003;Zanetti et al, 2005;Baena, et al, 2005), pois foi desenvolvido e validado por Zanetti et al (2006) para as condições climáticas do Brasil, e as séries sintéticas produzidas possuem informações associadas à precipitação importantes para o cálculo da erosividade, como precipitação total diária, duração do evento, intensidade máxima instantânea de precipitação, tempo de ocorrência da intensidade máxima e parâmetros que caracterizam o perfil da precipitação.…”
Section: Methodsunclassified
“…Como a variação sazonal da precipitação pluvial exerce forte influência sobre as condições ambientais, muitos pesquisadores vêm desenvolvendo estudos com base no número de dias chuvosos (Brunettia et al, 2001;Seleshi & Zanke, 2004;Zanetti et al, 2006;Modarres & Silva, 2007). Ainda sobre este assunto, Hess et al (1995) registraram que o decréscimo da precipitação no nordeste da zona árida da Nigéria resultou em decréscimo no número de dias chuvosos.…”
Section: Introductionunclassified